Strategi Manajemen Pembiayaan Pendidikan dalam Menunjang Keberlanjutan Madrasah Aliyah Daarul Muqimien Tangerang - Ahmad Tontowi Jauhari; Ara Hidayat (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
Educational financing management is a strategic factor in ensuring the sustainability of Islamic educational institutions, particularly private madrasas integrated with the Islamic boarding school system and facing limited funding sources. Madrasah Aliyah Daarul Muqimien Tangerang, as a boarding school-based madrasah, faces complex financing challenges to sustainably support formal education and Islamic boarding school programs. This study aims to analyze the educational financing management strategies implemented and their contribution to the institution's sustainability. This study uses a descriptive qualitative approach with a case study design. Data collection techniques were carried out through in-depth interviews, observation, and documentation, with research subjects including the madrasah principal, treasurer, teachers, and foundation managers. Data analysis was conducted using an interactive model that includes data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation of sources and techniques. The results of the study indicate that the financing management strategy at Madrasah Aliyah Daarul Muqimien is implemented in a planned manner through the preparation of the Work Plan and Budget (RKAM), the utilization of various funding sources, the application of efficiency principles and priority scales, and transparent monitoring and evaluation. This strategy contributes positively to the continuity of educational programs, institutional stability, and increased public trust. Thus, effective, accountable and Islamic-value-based financing management is an important key in supporting the sustainability of Islamic boarding school-based madrasas. Keywords: Educational Financing Management, Madrasah Sustainability, Islamic Boarding Schools, Madrasah Aliyah, Islamic Education   Abstrak Manajemen pembiayaan pendidikan merupakan faktor strategis dalam menjamin keberlanjutan lembaga pendidikan Islam, khususnya madrasah swasta yang terintegrasi dengan sistem pesantren dan memiliki keterbatasan sumber dana. Madrasah Aliyah Daarul Muqimien Tangerang sebagai madrasah berbasis boarding school menghadapi tantangan pembiayaan yang kompleks untuk menopang program pendidikan formal dan kepesantrenan secara berkelanjutan. Penelitian ini bertujuan untuk menganalisis strategi manajemen pembiayaan pendidikan yang diterapkan serta kontribusinya terhadap keberlanjutan lembaga. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan dokumentasi, dengan subjek penelitian meliputi kepala madrasah, bendahara, guru, dan pengelola yayasan. Analisis data dilakukan menggunakan model interaktif yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan, serta diuji keabsahannya melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa strategi manajemen pembiayaan di Madrasah Aliyah Daarul Muqimien dilaksanakan secara terencana melalui penyusunan RKAM, pemanfaatan berbagai sumber dana, penerapan prinsip efisiensi dan skala prioritas, serta pengawasan dan evaluasi yang transparan. Strategi tersebut berkontribusi positif terhadap kontinuitas program pendidikan, stabilitas kelembagaan, dan peningkatan kepercayaan masyarakat. Dengan demikian, manajemen pembiayaan yang efektif, akuntabel, dan berlandaskan nilai-nilai Islam menjadi kunci penting dalam menunjang keberlanjutan madrasah berbasis pesantren Kata kunci: Manajemen Pembiayaan Pendidikan, Keberlanjutan Madrasah, Pesantren, Madrasah Aliyah, Pendidikan Islam